Determine the impact of road humps on travel time [electronic resource] - Seyed Mehrdad Ghaemi, 1985- (2012)
Thesis (Sarjana Kejuruteraan (Awam - Pengangkutan dan Jalanraya)) - Universiti Teknologi Malaysia, 2012